2013
DOI: 10.1039/c3tc30818a
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency yellow organic light emitting diodes with a balanced carrier injection co-host structure

Abstract: We demonstrate herein the design and fabrication of a highly efficient yellow organic light-emitting diode (OLED) with a balanced carrier injection device architecture having a zero electron-injection-barrier host blended with a hole-injection aiding co-host. The resultant yellow OLED showed, at 1000 cd m À2 for example, an efficacy of 59 lm W À1 , current efficiency of 71 cd A À1 and external quantum efficiency (EQE) of 23%, with values of 42 lm W À1 , 47 cd A À1 and 15% EQE without a co-host. The co-host eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Furthermore, the efficiency roll‐off was low with EQEs of 31.5% at 1000 cd m − 2 and 28.2% at 10 000 cd m − 1 , and a PE of 66 lm W − 1 at 1000 cd m − 2 even without any extra out‐coupling structure. The achieved EQEs of the orange OLED are the highest ones reported up to date . The normalized electroluminescent (EL) spectrum of the device at a current density of 1 mA cm −2 is displayed in Figure e.…”
Section: Performance Of Orange and Tandem White Oleds At A Luminance mentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, the efficiency roll‐off was low with EQEs of 31.5% at 1000 cd m − 2 and 28.2% at 10 000 cd m − 1 , and a PE of 66 lm W − 1 at 1000 cd m − 2 even without any extra out‐coupling structure. The achieved EQEs of the orange OLED are the highest ones reported up to date . The normalized electroluminescent (EL) spectrum of the device at a current density of 1 mA cm −2 is displayed in Figure e.…”
Section: Performance Of Orange and Tandem White Oleds At A Luminance mentioning
confidence: 78%
“…The other way is to utilize both green‐ and red‐emitting phosphorescent materials. The latter method has advantages over the first method in terms of the color‐rendering index and color gamut because of the broad emission spectrum ranging from green to red even though higher efficiencies have been reported using single orange‐emitting dyes …”
Section: Performance Of Orange and Tandem White Oleds At A Luminance mentioning
confidence: 99%
“…It implies that bulk doped emitting layer architecture is much more hole dominating and the impact on the electron transport is almost negligible. Accordingly, it can be concluded that the use of the doped ultrathin emissive layer structure may provide excellent electron transport channel and thus balance the carrier flow in the emissive layer, leading to higher efficiencies in device C2 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a better carrier recombination within the emitting layer was achieved. [34] Furthermore, the device R1 presented quite better performance, even though the MTZ based single-carrier device shown a more balanced bipolar carrier-transporting ability than that of PTZ. A possible reason was that, generally, the migration rate of hole transport layer (HTL) was higher than that of electron transport layer (ETL) in the devices.…”
Section: Bipolar Transporting Characteristicsmentioning
confidence: 98%